Application of economic policy instruments in the management of natural resources with special focus on the concept of ecosystem services - Louda, Jiří (2016)
The dissertation deals with application of economic approaches and instruments in natural resource management. The paper puts a special emphasis on the developing concept of ecosystem services (mainly abroad) and its application in the Czech Republic's context. The objective of the thesis is to cultivate academic discussion of the importance of methods employed in environmental economics for application of economic policy tools in natural resource management in the Czech Republic's context and, among other things, to clarify whether (and if so, how) the concept of ecosystem services may contribute to the formulation of these tools. The paper also discusses possible limitations of using purely quantitative econometric methods in environmental policy. The dissertation is designed as a cumulative paper. The results of five scholarly articles presented document that application of economic approaches (such as valuation of environmental goods and services) may contribute to efficient meeting of environmental policy goals and that the ecosystem service concept brings new capabilities for application of economic theories in practical natural resource management. One of the new instruments grounded in this concept is the payments for ecosystem services, increasingly implemented abroad. However, the research results also point out the fact that isolated application of outcomes from quantitative environmental goods and services/ecosystems assessment methods has its limitations and may lead to design of measures and tools that will not have the desired effect. The recommendation is therefore to combine outcomes from quantitative methods with qualitative approaches (such as institutional analysis or stakeholder analysis).